Gingival fibroblast suppress the osteogenesis process mediated by bone substitute materials via WNT/β-catenin signaling pathway in vitro and in vivo - Liu, Guanqi; Lin, Jiahui; Chen, Xiaoyan; Liu, Runheng (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundThe regeneration of bone tissue is a critical challenge in oral and maxillofacial surgery, with the success of such procedures often depending on the ability to promote osteogenesis while managing the soft tissue environment. The role of gingival fibroblasts in modulating the osteogenic potential of mandible mesenchymal stem cells (MMSCs) mediated by bone substitute materials (BSMs) is not fully understood. This study aimed to investigate the impact of gingival fibroblasts on the osteogenic differentiation of MSCs in the presence of BSMs and to elucidate the underlying mechanisms, focusing on the WNT/β-catenin signaling pathway.MethodsGingival fibroblasts and BSMs co-culture conditioned medium was used to culture MMSCs, and the expression and activity of alkaline phosphatase (ALP), as well as osteogenic and fibrogenic gene and protein expression, were evaluated. Additionally, the expression of key factors of WNT/β-catenin signaling pathway were investigated. In vivo animal experiments were conducted to assess the effect of gingival fibroblasts on BSM-mediated bone regeneration.ResultsGingival fibroblasts and BSMs co-culture environment did not affect MMSCs proliferation but significantly inhibited ALP expression and activity, as well as osteogenic gene and protein expression, while promoting expression of fibrogenic markers. This suppression was associated with the downregulation of key factors in the WNT/β-catenin signaling pathway. In vivo, increased suppression of bone defect repair was observed with higher amounts of gingival fibroblasts, confirming the in vitro findings.ConclusionOur study demonstrates that gingival fibroblasts can suppress the osteogenic potential of BSMs by inhibiting the autocrine WNT expression and the activation of the WNT/β-catenin signaling pathway in MMSCs. These findings highlight the importance of considering the cellular microenvironment in tissue engineering and regenerative medicine and suggest potential targets for modulating MMSCs behavior to enhance bone regeneration.